Implementasi Digital Marketing UMKM Erni Cake and Cookies Desa Mojotengah Kecamatan Bareng Kabupaten Jombang - Alifia Siska Yuliana; Sishadiyati Sishadiyati; Wiwin Priana Primandhana (Cv. Utility Project Solution, 2023)
Digital marketing is a marketing activity that utilizes digital technology sophistication. By implementing digital marketing, business activities will be more efficient, and can increase the productivity of MSMEs. The focus of implementing digital marketing is the UMKM Erni Cake and Cookies whose business development has not optimally utilized information technology. The implementation method begins with conducting surveys and interviews, digital marketing outreach, mentoring, and evaluation. The platforms chosen as a means of product promotion are Facebook Marketplace, WhatsApp Business, and Instagram. The results obtained from the implementation of digital marketing at Erni Cake and Cookies UMKM are that UMKM owners feel helped and feel the impact such as interaction with new prospective buyers on one of the platforms used as a means of promotion. In order to maximize the use of digital marketing, a consistent attitude is needed in posting products on various platforms, so that it will attract new potential buyers.